Studi komparatif nilai kondisi perkerasan lentur di Ruas Jalan Sekargadung–Sidomulyo berdasarkan metode PCI dan SDI - Dafin Farianto; Sugeng Dwi Hartantyo; Romadhon (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
Public mobility and regional economic growth are heavily dependent on the quality of road infrastructure. However, high and repetitive traffic loads frequently trigger premature failure in flexible pavements. This study aims to identify the types and severity levels of distress, assess pavement conditions, and formulate maintenance recommendations for the Sekargadung-Sidomulyo road section in Gresik, East Java. Pavement condition assessment was conducted using the Pavement Condition Index (PCI) and Surface Distress Index (SDI) methods. The distresses identified in the field include depressions, rutting, patching, alligator cracking, bleeding, shoving, longitudinal cracking, potholes, raveling, block cracking, joint reflection cracking, and bumps. The results indicate an average PCI value of 69.3 and an SDI value of 49.5, both consistently classifying the road condition as